TINJAUAN KUAT TEKAN BETON MUTU TINGGI DENGAN PENAMBAHAN TALI TAMBANG PLASTIK - Abdul Rokhman; Dyah Pratiwi Kusumastuti (Sekolah Tinggi Teknik - PLN, 2016)
High quality concrete as a construction material more widely used, but the higher of the concrete qualitywill cause ductility properties of concrete decreases. One way to decimate the mechanical properties of highstrength concrete is to provide additional materials in the concrete mix. This study aimed to determine theeffect of plastic rope in the concrete mixture. Technical properties of concrete under review due to theaddition of plastic rope to concrete is compressive strength. The method used in this research is to make a testpiece for later testing compressive strength. The test object is created by the addition of plastic rope along the5 cm, 7 cm and 10 cm as much as 0.5% by weight of coarse aggregate. Specimens were made for eachvariation is 3 pieces and will be tested on the concrete age 7 and 28 days. The planned results in this study isthe high quality concrete compressive strength of 55 MPa at the age of concrete 28 days. From the researchthat at the age of concrete 28 days minimum compressive strength of concrete specimen contained in theconcrete with the addition of 5 cm plastic ropes of 11.75 MPa or 21.36% of the compressive strength ofconcrete plans. The maximum concrete compressive strength at 28 days there on the concrete specimen withthe addition of plastic rope 7 and 10 cm at 12.14 MPa or 22.07% of the compressive strength of concreteplans.